Cognitive Function and Self-Management Behaviors in Older Adults With Type 2 Diabetes. Issue 1 (10th January 2023) - Kim, Min Jung; Bronas, Ulf G.; Quinn, Laurie; Sharp, Lisa K.; Park, Chang; Gruss, Valerie; Fritschi, Cynthia
Abstract : Background: Type 2 diabetes (T2D) is strongly associated with cognitive impairment. Decreased cognitive function could affect daily self-management behaviors critical for people with T2D. Executive function is significant for daily self-management, and decreased subjective cognitive function could be an early indicator of poor daily self-management. However, little is known about whether executive or subjective cognitive function affects daily self-management behaviors in older adults. Objectives: We investigated the effect of executive function or subjective cognitive function on daily self-management behaviors (diet, glucose management, physical activity, and physician contact) in older adults with T2D. Methods: We used a cross-sectional, observational design with convenience sampling of 84 adults aged ≥60 years with T2D. Telephone-administered cognitive function tests measured participants' overall cognitive and executive function levels. Subjective cognitive function, diabetes self-management, and covariates, including demographic information (age, gender, race/ethnicity, and level of education), body mass index, depressive symptoms, and diabetes duration, were assessed using online surveys. Data were analyzed using bivariate correlation and backward stepwise regression. Results: The mean age of the sample was 68.46 ± 5.41 years. Participants were predominantly female and White, and the majority had normal cognitive function. Controlling for demographics, body mass index, depressive symptoms, and diabetes duration, a decrease in executive function indicated by a greater number of errors made during the telephone-administered Oral Trail Making Test Part B relative to the sample was associated with poorer adherence to physician contact behaviors. Subjective cognitive function was not associated with any self-management behaviors. Discussion: A reduction in executive function was associated with poorer adherence to physician contact behaviors in older adults with T2D and normal cognitive function; lack of adherence to physician contact behaviors could be an early indicator of declining cognitive function. Difficulties or changes in routine diabetes self-management behaviors should be closely monitored in older adults. Cognitive assessment should be followed when needed.